2017
DOI: 10.3390/robotics6040041
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Joint-Level Robot Programming with a New Robotics Software Tool

Abstract: Abstract:With the rising popularity of robotics in our modern world there is an increase in the number of engineering programs that offer the basic Introduction to Robotics course. This common introductory robotics course generally covers the fundamental theory of robotics including robot kinematics, dynamics, differential movements, trajectory planning and basic computer vision algorithms commonly used in the field of robotics. Joint programming, the task of writing a program that directly controls the robot'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…The main results in the questionnaire and interviews showed that the FIRST program had a strong influence on students' decision to study STEM domains. These results support and strengthen previous research outcomes [29][30][31][32], which indicated that participation in robotics competitions increase interpersonal skills and promote career choice in a STEM domain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main results in the questionnaire and interviews showed that the FIRST program had a strong influence on students' decision to study STEM domains. These results support and strengthen previous research outcomes [29][30][31][32], which indicated that participation in robotics competitions increase interpersonal skills and promote career choice in a STEM domain.…”
Section: Discussionsupporting
confidence: 90%
“…By building robots in teams, students can learn engineering skills such as teamwork skills, designing, and problem-solving. Using PBL in robotics helps improve the students' knowledge, while they gain the benefits of PBL [29,30].…”
Section: Roboticsmentioning
confidence: 99%
“…With all the advantages of AI, it has an obstacle to development and implementation -people express distrust of new technologies and often do not have the necessary knowledge. Users of information systems often confuse the concepts of artificial intelligence and robotics [13,14]. Non-AI programs execute a specific sequence of instructions, and AI systems, mimicking the human mind, are able to learn.…”
Section: Discussionmentioning
confidence: 99%
“…A simplified C language [27] eliminating some of its major features is proposed for robot education. This approach is classified as an external DSL [11] because its source code is parsed by Yacc [28] and does not support pass-by-reference and pointer operators as the features.…”
Section: Bottom-up Approachmentioning
confidence: 99%